The evaluation of the two-dimensional gamma passing rate efficiency for the unilateral breast cancer dosimetry using the Intensity-Modulated Radiation Therapy - Afnan Fouad Al-Wakeel,; Mustafa Salih. Al Musawi,; Hayder Hamza Alabedi, (Journal of the Pakistan Medical Association, 2024)
Objective: To evaluate the efficacy of the commonly used two-dimensional gamma passing rate of 3%/3mm for females with unilateral breast cancer. Method: The cross-sectional study was conducted at Al-Andalus Private Hospital, Baghdad, Iraq, from November 2021 to April 2022 after approval from the Medical Physics and Physiology Department of Mustansiriyah University, Baghdad, and comprised female patients with unilateral breast carcinomas. All the patients were subjected to a computed tomography simulation, and data was transferred to treatment planning system Monaco 5.1 for contouring and planning. An intensity-modulated radiation therapy method was selected. The planning comprised phantom detector and linear agility accelerator for pre-treatment verification. All patients were evaluated using two alternative dosimetry methods: 3%/3mm and 3%/2mm at the threshold of 10% and 5%. The Two-dimensional gamma analysis took each transversal slice in the simulation image for comparison. Data was analysed using SPSS 24. Results: There were 15 female patients aged 26-65 years. There was a better impact of 3%/3mm compared to 3%/2mm criterion for 5% and 10% thresholds. The proportion was 10% higher than the cutoff point of 5%. Conclusion: The 3%/2mm criterion should be used for plans that give a high dosage to organs at risk, while the 3 %/3 mm criterion should be used for uncomplicated situations with moderate dosages to at-risk organs. Key Words: Unilateral Breast, Tomography, Radiotherapy